Regulatory mechanisms of monopoly in conditions of the market economy - Ilkhomovich, Kholbaev Sanjar (Middle European Scientific Bulletin, 2021)
The article is devoted to study theoretical approaches to a monopoly concept from the point of view of the market economy, explore regulation practices of monopoly, legislation bases of antitrust policyin developed countries and conduct comparative research of used regulation methods of natural monopoly. Results of the research also lead to the ways of improvement of monopoly regulations in Uzbekistan in order to provide economic efficiency.